Situational Crime Prevention and Terrorism: An Assessment of 10 Years of Research. (December 2019) - Freilich, Joshua D.; Gruenewald, Jeff; Mandala, Marissa
This study systematically reviews the Situational Crime Prevention (SCP) and terrorism literature published between 2006 and 2016. We examine several variables related to the backgrounds of authors, publication outlets, methods used, and countries and terrorist groups focused upon in these studies. We also investigate if studies have tested the pillars of terrorism opportunity relating to weapons, targets, tools, and facilitating conditions. We find a strong literature and much support for SCP's claims in the terrorism context. We highlight some data and method obstacles in fully evaluating SCP's EVIL DONE, MURDEROUS, and ESEER frameworks and tools pillar, and suggest a need for more multivariate designs. We end by identifying underexplored substantive issues that deserve more attention, such as possibly refining EVIL DONE and to more fully address displacement versus adaptation processes.